CompTIA Network+ N10-007 - Sequeira, Anthony (Cert guide., 2018)
The CompTIA Network+ N10-007 Cert Guide has 10 accompanying videos that provide more than 60 minutes of training on two key exam topics: the OSI Model and IP Addressing. The first six videos provide an introduction to the OSI model and the seven layers of the model. The last four videos provide a review of the binary numbering system, a basic and advanced subnetting review, and an introduction to IPv6.